INDUSTRIAL EXTRACTION OF WESTERN AUSTRALIAN SANDALWOOD SEED OIL - Hettiarachchi, D. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Western Australian Sandalwood (Santalum spicatum) seed kernels have been used traditionally by indigenous Australians for dietary and medicinal purposes. An elaborate research on the seeds has revealed the abundance of a fixed oil in kernel which consist a rarer fatty acid (xymeninic acid). A pharmacological study of the above seed oil resulted body lipid regulatory and beneficial effects on skin. Sandalwood cultivations are producing considerable amount of seeds which are unused despite of its value, thus we decided to extract seed oil industrially which can be a potential nutraceutical or cosmetic agent. Common methods of cold press and extrusion were found to be unsatisfactory due to the presence of gum material in the kernel. Pre-treatment of kernel material was trialled with physical, chemical and biological means which result in no significant yield. Solvent extraction was successfully developed followed by an economical de-gumming method. Oil of expected quality was yielded in higher percentage but the method was subjected to uncertainty due to developing global trend and legal constrains on solvent extracted plant material for human consumption. Super critical carbon dioxide extraction was experimented as a newer economical method. Above experimented method has resulted higher yields and oil which complies with standards. This less hazardous method produces oil free of contaminants and also makes the exhausted meal clean for any further uses. A recent feasibility study on this method has predicted over 50t production of oil per annum.